Prevention Of Bullying Among Adolescents In The Lens Of Indonesian Policy And Law: Should Nurses Know? - Wuryaningsih, Emi Wuri; Wahyuni, Budi; Lusmilasari, Lely; Haryanti, Fitri (Universitas Airlangga, 2022)
Introduction: Indonesia has several institutions, policies, and laws to protect children from all forms of violence, including bullying that impacts physical, psychological, and social health and even death. However, the number of cases of bullying in adolescents still increases. It is related to a lack of knowledge about bullying and is associated with norms in the community. Method: The analysis uses a discourse analysis approach,